Hyperplastic, dysplastic and neoplastic lesions associated with a model of carcinogenesis induced by DMBA in the salivary glands of BALB-c mice - Carino, Silvia (2024)
The aim of this work was to develop a mouse model of submandibular salivary gland carcinogenesis by chemical induction and to perform a revision of the literature on similar models using the carcinogen 7,12-Dimethylbenz[a]anthracene (DMBA). The descriptive review was carried out on published works in English and Spanish languages, from the period 1977-2023, which included different animal models of chemical carcinogenesis induced by DMBA in salivary glands. Articles were reviewed in order to analyze the effectiveness of the carcinogenesis induction. For our model, BALB/c mice were used. Animals were anesthetized and after surgery to expose the submandibular gland, each mouse was injected with solution of DMBA 2% in corn oil. Mice were monitored weekly until sacrifice at week 12. The samples were processed with the routine histological methods. The results from the descriptive review showed that DMBA is mainly administered by Intraglandular injections into the submandibular glands after surgical exposure, being both pellets and solutions used for the induction, and rats more common than mice. This revision summarizes the research results of previous studies and demonstrates which model has greater reproducibility. Our results showed that one single injection of DMBA directly into the surgically exposed submandibular gland was an optimal technique to induce the tumor at the desired site. Edema was observed in the surgical area during the first 2 weeks. From week 5, the mice presented internal hardness and hair loss in the glandular area; 50% of the animals presented palpable and measurable tumor masses from week 10. Microscopic observations showed that 89% of the mice developed malignant neoplasms: Carcinomas in situ, micro-invasive and invasive (6/8); sarcomas (1/8), and carcinosarcoma (1/8). Associated lesions were atypical ductal hyperplasia; periductal fibrosis, and sarcomatous stroma. This model marks a difference with the subcutaneous injection technique, without surgery, which does not allow the carcinogen to be adequately directed to the gland.